Preparation, characterization and methylene blue adsorption of surfactant-templated mesoporous carbon coated monolith - Malekbala, Mohamad Rasool (2012)
This thesis work brings the preparation and characterization of mesoporous carbon coated monolith (MCCM) by using nonionic surfactant as template and its application on adsorption of methylene blue. MCCM with high surface area and pore volume was synthesized and characterized in detail. The preparation of mesoporous carbon coated monoliths consisted of polymerization, dip-coating,solidification and carbonization. MCCM have been prepared by dip-coating cordierite monoliths in a polymer solution consists of furfuryl alcohol (carbon source), F127 (template), pyrrole (binder) and nitric acid (polymerization catalyst). After solidification of the polymer, the coating was carbonized at temperature of 700 oC to obtain MCCM. The influence of concentration of the surfactant template in MCCM was investigated. It was found that by increasing the concentration of surfactant, adsorption capacity of MCCM increases from 100 to 200 mg/g. The mesoporous carbon coated monoliths are characterized by nitrogen adsorptiondesorption,thermogeravimetric analysis, scanning electron microscopy and Fourier transform infrared. The characterization study shows that the MCCM prepared in this work possesses a higher surface area (842 m2/g), pore volume (0.3 m3/g) and mesoporosity (97%) compare to previous study (MCCM by PEG). The potential of mesoporous carbon coated monolith on the adsorption of methylene blue dye was investigated. Batch adsorption experiments were carried out to find out the effects of pH (2-11), salt, contact times (4480 min), initial dye concentrations (50-400 ppm) and temperature (25, 35 and 45 oC) on the adsorption of the dye. pH was found to be the most significant factor and pH 10 was favorable for MB adsorption. Furthermore, kinetic study showed that the adsorption could be better represented by the pseudo-second-order model. Equilibrium adsorption data were predicted by two isotherms, i.e. the Langmuir and the Freundlich isotherms. The best fit to the data was obtained with the Langmuir isotherm with maximum monolayer adsorption capacity of 388 mg/g. Adsorption of MB is favourably influenced by an increase in the temperature of the operation from 388 to 440 mg/g. By associated thermodynamic parameters, the adsorption was found to be spontaneous and endothermic. Desorption study indicates that 0.1N hydrochloric acid exhibits higher elution efficiency and a quantitative recovery of MB (around 82%) can be achieved.